-Ermanita Permatasari STAI Darusalam Perlindungan Terhadap Anak Sebagai Pelaku dan Korban Tindak Pidana di MTS dan MA - Ermanita Permatasari (Nizham Jurnal Studi Keislaman, 2017)
Children are the trust and grace of God Almighty, which have values as a whole person. Children also have human right that appreciates by people of the world. In physical and mental growth period, children need care, special protection, and legal protection both before and after birth. It should be admitted that the family is a natural environment for the growth and welfare of children. The protection of children's rights receives less attention from various parties, including concrete steps to protect children's rights. Labuhan Ratu Sub-district of Lampung Timur Regency is one of East Lampung Regency with juvenile delinquency data which is 3 (three) MTs and 1 (MA). In MTs and MA in Labuhan Ratu sub-district, Lampung Timur District, there are various types of juvenile delinquency (Juvenile Delinquency) caused by the child's own condition, physical and social. Increasing the number of violations for child offenders in conflict with the law is also evident from the data held by Unit PPA (Protection of Women and Children) Lampung Timur Police. During the year 2016, there were 57 children in Labuhan Ratu sub-district who had problems with the law both as perpetrators and as victims Juvenile delinquency cases, ranging from immorality, Persecution, Pornography, theft, violence, etc. that occurred in MTs and MA in Labuhan Ratu sub-districts are still largely handled by schools, involving parents, and communities. But also not a few who finally proceed with the reporting process to the police. Associated with the child's capacity as a perpetrator generally end up thrown into jail or prison house. Whereas the Prison Crime should be the last alternative (Ultimum Remedium). It can be argued that 90% of children facing the judicial process were sentenced to a conviction (jail).